Carbon and nutrient accumulation in mangrove sediments affected by multiple environmental changes - Perez, Alexander (2020)
Purpose In order to assess the impact of anthropogenic activities on carbon and nutrient accumulation, total organic carbon (TOC), nitrogen (TN), and phosphorus (TP) accumulation rates were examined in a Pb-210-dated mangrove sediment core from Sepetiba Bay, Brazil, a coastal region impacted by multiple environmental changes during the previous century. Materials and methods A 50-cm length sediment core was collected from a mangrove forest in Sepetiba Bay. Sediment subsamples were analyzed to measure TOC, TN, delta C-13, and delta N-15 using an elemental analyzer attached to an isotope ratio mass spectrometer Thermo Finnigan Model Delta Plus XP, whereas colorimetric analysis were used to measure TP. For (210)Pbex analyses, gamma-ray measurements were performed in a semiplanar intrinsic germanium high purity coaxial detector, coupled to a multichannel analyzer, whereas the sediment accumulation rate (SAR) was calculated according to the constant initial concentration (CIC) method. Also, carbon and nutrient fluxes were calculated using SAR and TOC, TN, and TP contents, whereas statistical differences were evaluated by ANOVA + Tukey HSD analysis with previous data normalization. Results and discussion The calculated sedimentation rate (similar to 8.1 mm year(-1)) since the early 1900s was up to threefold higher than the global mean determined for mangrove forests (similar to 2.8 mm year(-1)) and the regional sea level rise (similar to 3.2 mm year(-1)). Significantly higher TOC, TN, and TP fluxes, up to nearly 1000, 90, and 15 g m(-2) year(-1), respectively, were observed after the water diversion from a nearby drainage basin in the 1950s and an increase in sewage effluent input, which increased in the early 1990s. After this period, lighter delta C-13 values (similar to - 25 parts per thousand) indicate an increased importance of the terrestrial organic matter source, while lower TOC:TN ratios (similar to 11) and heavier delta N-15 values (similar to + 9 parts per thousand) suggest an increased influence of anthropogenic fertilization on inorganic nitrogen accumulation. Conclusions The significantly higher accumulation rates during the last decades evidenced the role of mangrove sediments as sinks for anthropogenically enhanced inputs of carbon and nutrients. Also, studies on carbon and nutrient accumulation evidenced the need for further research in eutrophic coastal areas.